Towards a common institutional trajectory? Individual complaints before UN treaty bodies during their ‘Booming’ years - Cali, Basak; Galand, Alexandre Skander (International journal of human rights, 2020)
The expanding number of UN treaty bodies with competence to rule on individual complaints as well as the increasing amount of complaints lodged before these bodies trigger the question whether they are capable of acting as a unified institution when dealing with individual complaints or whether they remain as a fragmented institutional site. In this article, we comparatively analyse the case law of all treaty bodies between 2013 and 2016 with the aim of assessing whether UN treaty bodies are moving towards a common institutional trajectory. We find that despite textual differences, the treaty bodies’ case law displays both early signs of a common institutional trajectory and risks of institutional fragmentation. The most significant common institutional trends are access friendliness; self-referential citations, a preference for implicit harmonisation; and case by case activism with respect to individual remedies. Yet, we also identify lack of systematic and explicit cross treaty-fertilization and diverging approaches to specifying general remedies as risks that may undermine the formation of a common institutional trajectory. We argue that the early signs of informal collective institutionalisation may be capable of fostering a common institutional identity in the years to come, if risks of fragmentation are acknowledge and mitigated.
CRIS-Team Scopus Importer:2023-03-21
Keywords: comparative international human rights law; fragmentation; human rights remedies; UN treaty bodies; UN treaty body reform